ANALSIS SEKTOR UNGGULAN KABUPATEN TAPANULI UTARA - Sonia Utami Sinurat; Evalina Pakpahan (VALUE, 2022)
It is very important to know the leading sector in an area; to determine the determinants of economic growth in a region; and to estimate the growth prospects of the regional economic sector in the future. The data analysis technique used in this study is Location Quotient Analysis (LQ Analysis); Shiftshare Analysis; and Klassen Typology Analysis. Location Qoutient Analysis (LQ Analysis) is used to determine the leading sector in an area. The results of the Location Quotient analysis (LQ analysis) show that there is one sector that is currently a leading sector but does not have the potential to excel in the future. There are three sectors that are currently leading sectors and have the potential to excel in the future. There are nine sectors that are not currently superior and have no potential to excel in the future. And there are three sectors that are not currently leading sectors but have the potential to excel in the future.